Design & Development of Used Cooking Oil (UCO) Container with IoT Approach - CHE HAMID, MUHAMMAD FARHAN SYAH BIN; Abd Fathul Hakim Zulkifli (Progress in Engineering Application and Technology, 2025)
Improper disposal of used cooking oil (UCO) poses significant environmental risks, including water pollution and drainage system blockages. Addressing these challenges is essential for promoting sustainable waste management practices and mitigating environmental harm. There is a growing need for innovative solutions to enhance UCO collection and management. This study aims to design and develop a smart container for used cooking oil collection integrated with IoT technology to optimize waste management process. The container is equipped with IoT technology sensor to monitor oil level, transmitting real-time data to a mobile application. The proposed solution involves a cylindrical container equipped with IoT-enabled ultrasonic sensor to monitor oil levels and display real-time data on an LCD screen. The system also features wireless connectivity via NodeMCU, enabling notifications through the Blynk application when the container is full. The design focuses on ease of use, durability and efficient data communication using low-power wireless protocols. The developed prototype is expected to improve the efficiency of UCO collection by providing realtime monitoring and alerts. This innovation aims to reduce improper UCO disposal and promote sustainable practices. This project demonstrates the potential of IoT technology in addressing environmental challenges, offering a scalable and sustainable solution for UCO management